Sequence polymorphism and PCR-restriction fragment length polymorphism analysis of the flagellin gene of Burkholderia pseudomallei. - Tay, S.T.; Cheah, P.C.; Puthucheary, S.D. (American Society for Microbiology, 2010)
Four flagellin allelic types (I to IV) of Burkholderia pseudomallei were identified based on their sequence variation and restriction fragment length polymorphism (RFLP) analysis of the amplified flagellin gene. Flagellin allelic type I was the most predominantly (75.0%) found among the 100 clinical isolates of B. pseudomallei investigated in this study.